Phylogeny Predicts the Quantity of Antimalarial Alkaloids within the Iconic Yellow Cinchona Bark (Rubiaceae: Cinchona calisaya) - Maldonado, Carla; Barnes, Christopher J.; Cornett, Claus; Holmfred, Else; Hansen, Steen H.; Persson, Claes; Antonelli, Alexandre; Rønsted, Nina (Frontiers in Plant Science, 2017)
Considerable inter- and intraspecific variation with respect to the quantity and composition of plant natural products exists. The processes that drive this variation remain largely unknown. Understanding which factors determine chemical diversity has the potential to shed light on plant defenses against herbivores and diseases and accelerate drug discovery. For centuries, Cinchona alkaloids were the primary treatment of malaria. Using Cinchona calisaya as a model, we generated genetic profiles of leaf samples from four plastid (trnL-F, matK, rps16 and ndhF) and one nuclear (ITS) DNA regions from twenty-two Cinchona calisaya stands sampled in the Yungas region of La Paz (Bolivia). Climatic and soil parameters were characterized and bark samples were analyzed for content of the four major alkaloids using HPLC-UV to explore the utility of evolutionary history (phylogeny) in determining variation within species of these compounds under natural conditions. A significant phylogenetic signal was found for the content of two out of four major Cinchona alkaloids (quinine and cinchonidine) and their total content. Climatic parameters, primarily driven by changing altitude, predicted 20.2% of the overall alkaloid variation, and geographical separation accounted for a further 9.7%. A clade of high alkaloid producing trees was identified that spanned a narrow range of altitudes, from 1,100 to 1,350 m. However, climate expressed by altitude was not a significant driver when accounting for phylogeny, suggesting that the chemical diversity is primarily driven by phylogeny. Comparisons of the relative effects of both environmental and genetic variability in determining plant chemical diversity have scarcely been performed at the genotypic level. In this study we demonstrate there is an essential need to do so if the extensive genotypic variation in plant biochemistry is to be fully understood.